The Value of an Educated Population for an Individual's Entrepreneurship Success - Jose Maria Millan; Emilio Congregado; Concepcion Roman; Mirjam van Praag; Andre van Stel (Tinbergen Institute, 2011)
Human capital obtained through education has been shown to be one of the strongest drivers of entrepreneurship performance. The entrepreneur's human capital is, though, only one of the input factors into the production process of her venture. The value of other input factors, such as (knowledge) capital and labor is likely to be affected by the education level of the possible stakeholders in the entrepreneur's venture. The education distribution of the (local) population may thus shape the supply function of the entrepreneur. Likewise, the demand function faced by the entrepreneur is also likely to be shaped by the taste, sophistication and thus the education level of the population in their role as consumers. In other words, a population with a higher education level may be associated with (i) a working population of higher quality; (ii) more and/or higher quality universities with a positive effect on research and development (R&D) and knowledge spillovers leading to more high tech and innovative ventures; and finally, (iii) a more sophisticated consumer market. Based on this, we formulate the following proposition: The performance of an entrepreneur is not only affected positively by her own education level but in addition, also by the education level of the population. We test this proposition using an eight years (1994-2001) panel of labor market participants in the EU-15 countries from which we select individuals who have been observed as entrepreneurs. We find strong support for a positive relationship between enrolment rates in tertiary education in country j and year t and several measures of the performance of individual entrepreneurs in that same country and year, including survival and the probability that an entrepreneur starts employing personnel and maintains as an employer for a longer period of time. An implication of our novel finding is that entrepreneurship and higher education policies should be considered in tandem with each other.
Keywords: J21; J23; J24; L22; L26; 330; entrepreneurship; performance; survival; personnel; education